El control patrimonial y la administración de bienes muebles en la Municipalidad Provincial de Ucayali - Contamana, periodo 2022 - Navarro Ruiz, Maria Luisa (2023)
The objective of this research was to determine the relationship between patrimonial control and the administration of movable property in the Provincial Municipality of Ucayali - Contamana, period 2022, opted for an applied type study, descriptive level - correlation and non-experimental design, whose population of study was 89 workers of said institution, for data collection the survey was used as a technique and the questionnaire as an instrument. In the result, it was established that the patrimonial control is being carried out on a regular basis, this is because the procedures for registering assets are sometimes adequate and that public auctions of movable assets are never carried out once a year. On the other hand, the administration of personal property is classified as regular since the institution almost always carries out an adequate procedure for asset control, facilitating the correct performance of its functions; in the same way, movable property on the part of those responsible is sometimes established according to the current norm. Finally, there is a significant relationship between heritage and the administration of movable property in the Provincial Municipality of Ucayali Contamana period 2022 with a Pearson correlation coefficient of 0.752 and a significance of 0.000.